Benthic foraminiferal assemblages from cold water coral habitats off northwest Scotland - Meryem Mojtahid; Magali Schweizer; Mélanie Douarin; Justine Gabriel; Christophe Colin; Nadine Tisnérat-Laborde; Mary Elliot (PANGAEA, 2021)
The dataset compiles counts of fossil benthic foraminifera from 69 sediment samples collected from marine sediment core +59-07/293VE retrieved in cold-water coral mounds. Vibrocore +59-07/293VE (59°43.40?N; 06°28.90?W) was retrieved at 282 m water depth with a total recovery of 495 cm during a British Geological Survey campaign in August 1984, at the junction with the Wyville Thomson Ridge and the West Shetland shelf/Hebridean shelf off northwest Scotland onboard the MV British Enterprise Four (Long et al., 1999). Foraminiferal assemblage data was collected in 2015, and the resulting record covers the last glacial period to the late Holocene. The purpose was to i) better constrain the paleoenvironmental changes that took place in the region since the last glacial time and ii) define the environmental conditions that allowed the onset, formation and decline of cold-water corals in this area.